O005 Cognitive behavioural therapy and light dark therapy for postpartum insomnia symptoms: a randomised controlled trial. (7th October 2021) - Verma, S; Quin, N; Astbury, L; Wellecke, C; Wiley, J; Davey, M; Rajaratnam, S; Bei, B
Abstract: Introduction: Symptoms of postpartum insomnia are common however interventions remain scarce. Cognitive Behavioural Therapy (CBT) and Light Dark Therapy (LDT) target distinct mechanisms to improve sleep. This randomised controlled superiority trial compared CBT and LDT against treatment-as-usual (TAU) in reducing maternal postpartum insomnia symptoms. Methods: Nulliparous females 4–12 months postpartum with self-reported symptoms of insomnia (Insomnia Severity Index scores >7) were included; excluded were those at risk or with high medical/psychiatric needs. Eligible participants were randomised 1:1:1 to 6 weeks of CBT, LDT (gaining light upon awakening, night-time light avoidance) or TAU. Interventions were therapist-assisted through two telephone calls and included automated self-help emails over six weeks. Symptoms of insomnia (ISI; primary outcome), sleep disturbance, fatigue, sleepiness, depression, and anxiety were assessed at baseline, mid-intervention, post-intervention, and 1-month post-intervention. Latent growth models were used. Results: 114 participants (mean age=32.2±4.6 years) were randomised. There were significantly greater reductions in insomnia and sleep disturbance in both intervention groups with very large effect sizes (d>1·4, p<0·0001) from baseline to post-intervention compared to TAU; improvements were maintained at one-month follow-up. There were greater reductions in fatigue symptoms in the CBT group (d=0.85, p<.0001) but not LDT (p=0.11) compared to TAU; gains were maintained for CBT at follow-up. Changes in sleepiness, depression and anxiety over time were non-significant compared to TAU (p-values>0.08). Conclusion: Therapist-assisted CBT and LDT are both efficacious for reducing postpartum insomnia symptoms. Findings were mixed for fatigue, sleepiness and mood. Future research is needed on predictors of treatment response.